Implementation of akad tahkim in sharia arbitration mechanism by Basyarnas-MUI - Firdaus, Muh. Nur Ridho Chaerul; Dahlan, Muh. Nur Fithri; Hidayat, Auliyya Anfasyah; Isnanjaya, Lutfi (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
Sharia arbitration as an alternative to sharia economic dispute resolution is still considered ineffective. In fact, when referring to the term “sharia” attached to sharia arbitration and Basyarnas-MUI, this institution should be a solution in accordance with the principles of Islamic law. This research aims to analyze the procedures and mechanisms of sharia arbitration by Basyarnas-MUI as well as the implementation of tahkim contracts in its implementation. This research uses a qualitative method with a literature study approach and a descriptive-analytical method based on the theory of tahkim contracts. The results show that there are six stages in the mechanism of sharia arbitration by Basyarnas, namely: (1) application registration, (2) arbitrator determination, (3) examination and trial process, (4) peace mediation, (5) decision making, and (6) execution and annulment of the decision. This study found that the implementation of the tahkim contract by Basyarnas has been carried out in principle, but not fully maximized, especially in the aspects of arbitrator competence and the validity of the object of dispute. Therefore, it can be concluded that the implementation of the tahkim contract in the sharia arbitration mechanism by Basyarnas-MUI still requires strengthening so that it can run in accordance with the principles of Islamic law and become an effective solution in resolving sharia economic disputes.